Influence of polarization on breakdown strength of polymeric composite dielectrics; Science, Measurement & Technology; Vol. 148, № 3 (May) - Gefle O. S.; Lebedev S. M.; Pokholkov Y. P. Yuri Petrovich; Agoris D. P.; Vitellas I. (2001, 2001)
The results of a study of electrical characteristics such as permittivity ϵ, loss factor tanδ and breakdown strength E b of new composite materials on the basis of polyvinylchloride filled with ferroelectric ceramic powder PZT are presented. It is shown that preliminary polarisation of composite materials by unipolar impulses of voltage enables the Eb of composites to be increased by a factor of 1.3-1.5 in comparison with nonpolarised composites. It is discovered that the value of the specific accumulated energy may be increased up to 105 J/m3. These composite materials can be used both for the electric field control in the insulation designs and for manufacture of capacitive stores of energy